2010
DOI: 10.1007/s10554-010-9681-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and extent of coronary artery disease determined by 64-slice CTA in patients with zero coronary calcium score

Abstract: The purpose of the study was to assess the presence and extent of atherosclerosis determined by 64-slice CTA in patients with 0 coronary calcium score (CACS) and to evaluate the affect of demographic features and risk factors on the atheroma burden of these patients. 883 cases (378 (42.8%) male, 505 (57.2%) female, mean age 51.28) with zero CACS were included in the study. Cases underwent CTA because of carrying risk factors or having chest pain or atypical symptoms. A non-enhanced CT scan was obtained for cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
(45 reference statements)
0
23
1
Order By: Relevance
“…Similarly, Kelly et al (14) and Ergün et al (13) found that the mean age of the cases with atherosclerotic plaque, as detected by coronary CT angiography (53 and 54.4 years, respectively), was higher than the mean age of the cases (49 and 50.4 years, respectively). The mean age of the cases with atherosclerotic plaques that caused significant stenosis, as detected by coronary CT angiography, was 54 years according to Kelly et al (14) and 55.2 years according to Ergün et al (13); however, we found that the mean age of these cases was 53.8 years in our study.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Similarly, Kelly et al (14) and Ergün et al (13) found that the mean age of the cases with atherosclerotic plaque, as detected by coronary CT angiography (53 and 54.4 years, respectively), was higher than the mean age of the cases (49 and 50.4 years, respectively). The mean age of the cases with atherosclerotic plaques that caused significant stenosis, as detected by coronary CT angiography, was 54 years according to Kelly et al (14) and 55.2 years according to Ergün et al (13); however, we found that the mean age of these cases was 53.8 years in our study.…”
Section: Discussionmentioning
confidence: 85%
“…In a study by Akram et al (15), the rate of obstructive plaques in symptomatic patients with a CAC score of zero was 8.2%, whereas obstructive plaques were not detected in asymptomatic patients. However, Kelly et al (14) and Ergün et al (13) did not find a correlation between symptoms and obstructive and nonobstructive lesions. In our study, we did not find a correlation between the presence of noncalcified atherosclerotic plaques that were detected using coronary CT angiography in a symptomatic patient population with a CAC score of zero.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Predictive factors for the presence of NCP in patients with zero CACS have also been described in several articles. Ergün et al reported that age and DM are associated with positive CTCA findings [14]. Uretsky et al reported that age (>60 years), male gender and a current smoking history are associated with a greater tendency to have coronary plaque [15].…”
Section: Discussionmentioning
confidence: 99%